SSR markers for grain iron zinc and yield-related traits polymorphic between Samba Mahsuri (BPT5204) and a wild rice Oryza rufipogon - Gowthami Chandu, Krishnam Raju Addanki, Divya Balakrishnan, Satendra K Mangrauthia, P. Sudhakar, A. Krishna Satya and Sarla Neelamraju (Electronic Journal of Plant Breeding, 2020)
Identification of molecular markers revealing polymorphism among the parental lines are prerequisite for mapping QTLs and genes for desired traits. The genomic regions which contributes to the accumulation of grain iron and zinc in rice could greatly help in rice bio fortification programs. A BC4F10 mapping population was earlier developed from the cross between an elite fine-grain Oryza sativa indica cultivar, BPT5204 and a wild progenitor specie O. rufipogon WR119. A total of 800 randomly selected SSR markers distributed on all the 12 chromosomes of rice including 50 gene specific markers related to grain iron, zinc and yield traits were used to identify the polymorphic loci between the two genotypes. In all, 166 markers (20.75 %) showed distinct polymorphism. 149 SSR markers (19%) out of 750 SSRs and 17 out of 50 gene-specific markers (36%) were polymorphic. The 17 polymorphic gene-specific markers were related to gene families OsZIP, OsYSL, OsNRAMP, OsNAAT, OsFRO, OsFDH, OsGSTU and OsPDR which are involved in metal transport and homeostasis in rice. Among the markers reported to be significantly associated with QTLs for grain iron, zinc and yield related traits, RM517, RM81A, RM264, OsYSL-7, RM5460, RM3874 were polymorphic in this study.